Georisk design approach for sustainable development on Mountainous Terrain / M.Z. Ghania and Z. Mohamed - Ghania, M.Z; Mohamed, Z. (2012)
Residential on or near mountainous terrain is becoming a popular life style partly owing to deficiency in flat land. However, it is subjected to risk of slope instability and slope hazards. Studies reported that slope hazards are commonly triggered by monsoon rain, human activities, deforestation or design and construction challenges. Slope hazard is identified as one of the frequent natural disasters that leads to fatalities and economic loss. Record shows that the past slope hazards in Malaysia had killed more than 500 peoples for the last forty years where the estimated economic loss is about 2.5 billion Malaysia Ringgit. This paper introduces the georisk and reliability design approach to predict the sustainability of development on or near mountainous terrains. A field study was conducted on fifty two slopes to identify the most frequent factor that trigger slope instability. Parameters such as slope geology, mode of slope failure, slope geometry, slope distress, rainfall, and drainage system and slope stabilization techniquewere studied. Further parametric study was carried out to determine the internal instability factor of slope failure.